GAMBARAN BEBERAPA FAKTOR RISIKO OBESITAS PADA WARGA BINAAN (Studi di Lembaga Pemasyarakatan Klas IIA Wanita Kota Semarang) - Silfiya Silfiya; Henry Setyawan Susanto; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Obesity is an excessive accumulation of fat tissue. This type of research is descriptive analytic with cross sectional design. The sampling technique is simple random sampling. The anthropometry is measured with Global Physical Activity Questionnares (GPAQ), and Depression Anxiety Stress Scale (DASS). Data analysis using chi square test. Sample in this study amounted 100 persons.The results showthere arenumber of parity, contraception using, a history of smoking, a history of alcohol consumption,physical activity,frecuency of snack consumption,and family support. Suggestions which are given to inmates such as control the weight with limiting the consumption of snack also consume more healthy foods like fruits and vegetables. Besides for correctional institution education and nutrition health check-up regularly.